2010
DOI: 10.4103/0019-557x.70537
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in prevalence of hypertension: Implications for interpretation

Abstract: Significant increase in prevalence of hypertension during winter compared to summer indicates need for considering this factor while comparing prevalence reported in different studies as well as interpreting the surveillance data based on repeat surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…Сезонная вариабельность артериального давления (АД) показана во многих исследованиях у лиц различных воз-растов, как с нормальным уровнем АД, так и у больных АГ tients [18][19][20][21]. Systolic and diastolic BP are characterized by peaks during both winter and summer periods.…”
Section: Winter Cardiovascular Morbidity In Ivanovo Region сердечно-сunclassified
See 1 more Smart Citation
“…Сезонная вариабельность артериального давления (АД) показана во многих исследованиях у лиц различных воз-растов, как с нормальным уровнем АД, так и у больных АГ tients [18][19][20][21]. Systolic and diastolic BP are characterized by peaks during both winter and summer periods.…”
Section: Winter Cardiovascular Morbidity In Ivanovo Region сердечно-сunclassified
“…Mean values of EWMI for stroke for the five years of followup were slightly negative. The only exception was 2011 year with the excess winter morbidity of [18][19][20][21]. И систолическое, и диастолическое АД характе-ризуются пиками как в зимний, так и в летний период.…”
Section: Winter Cardiovascular Morbidity In Ivanovo Region сердечно-сunclassified
“…It is similar to previous studies which showed that cold induced a sharp rise in BP and heart rate which are more marked in the first few minutes. 7,8 In this study, also significant rise in BP was seen after cold exposure in the first five minutes which came down towards baseline during the next five minutes. Moreover, in this study rise in diastolic BP was found to be more than rise in systolic BP.…”
Section: Discussionmentioning
confidence: 66%
“…The issue is also important for surveillance as data collected in different seasons may not find true trends. [19] Significant increase in SBP and DBP during winter may be for several reasons viz. external temperature, physical activity, seasonal variation in noradrenalin, catecholamine and vasopressin, vitamin D, and serum cholesterol among others.…”
Section: Discussionmentioning
confidence: 99%